Cut-off value of total adiponectin for managing risk of developing metabolic syndrome in male Japanese workers. - Akiko Hata; Koji Yonemoto; Yosuke Shikama; Nanako Aki; Chisato Kosugi; Ayako Tamura; Takako Ichihara; Takako Minagawa; Yumi Kuwamura; Masashi Miyoshi; Takayuki Nakao; Makoto Funaki (PLoS ONE, 2015)
Aim To determine the optimal cut-off value of serum total adiponectin for managing the risk of developing metabolic syndrome (MetS) in male Japanese workers. Methods A total of 365 subjects without MetS aged 20-60 years were followed up prospectively for a mean of 3.1 years. The accelerated failure-time model was used to estimate time ratio (TR) and cut-off value for developing MetS. Results During follow-up, 45 subjects developed MetS. Age-adjusted TR significantly declined with decreasing total adiponectin level (≤ 4.9, 5.0-6.6, 6.7-8.8 and ≥ 8.9 μg/ml, P for trend = 0.003). In multivariate analyses, TR of MetS was 0.12 (95% CI 0.02-0.78; P = 0.03) in subjects with total adiponectin level of 5.0-6.6 μg/ml, and 0.15 (95% CI 0.02-0.97; P = 0.047) in subjects with total adiponectin level ≤ 4.9 μg/ml compared with those with total adiponectin level ≥ 8.9 μg/ml. The accelerated failure-time model showed that the optimal cut-off value of total adiponectin for managing the risk of developing MetS was 6.2 μg/ml. In the multivariate-adjusted model, the mean time to the development of MetS was 78% shorter for total adiponectin level ≤ 6.2 μg/ml compared with > 6.2 μg/ml (TR 0.22, 95% CI: 0.08-0.64, P = 0.005). Conclusion Our findings suggest that the cut-off value for managing the risk of developing MetS is 6.2 μg/ml in male Japanese workers. Subjects with total adiponectin level ≤ 6.2 μg/ml developed MetS more rapidly than did those with total adiponectin level > 6.2 μg/ml.